1999
DOI: 10.1023/a:1008364727071
|View full text |Cite
|
Sign up to set email alerts
|

High antitumour activity of ET743 against human tumour xenografts from melanoma, non-small-cell lung and ovarian cancer

Abstract: ET743 is a very effective agent in chemo-sensitive and marginal chemo-resistant xenografts, but inactive in chemo-resistant tumour xenografts. The activity of ET743 in the marginally cisplatin-resistant ovarian cancer HOC18 might indicate absence or incomplete cross-resistance against cisplatin. It is recommended to include melanoma, non-small-cell lung cancer, and ovarian cancer in phase II clinical trials and to use an intermittent schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 15 publications
0
44
0
Order By: Relevance
“…In a preclinical study, trabectedin showed significant antitumor activity in vitro and in vivo against a range of solid tumor cells, including soft-tissue sarcoma (STS), ovarian, breast, prostate, and renal cancers; melanoma; and non-small-cell lung cancer (8)(9)(10)(11). On the basis of the promising results of preclinical and clinical studies (10,12,13), trabectedin is now approved in Europe for the treatment of STS after anthracycline and ifosfamide failure and for treating patients who cannot receive these agents (14).…”
Section: Introductionmentioning
confidence: 99%
“…In a preclinical study, trabectedin showed significant antitumor activity in vitro and in vivo against a range of solid tumor cells, including soft-tissue sarcoma (STS), ovarian, breast, prostate, and renal cancers; melanoma; and non-small-cell lung cancer (8)(9)(10)(11). On the basis of the promising results of preclinical and clinical studies (10,12,13), trabectedin is now approved in Europe for the treatment of STS after anthracycline and ifosfamide failure and for treating patients who cannot receive these agents (14).…”
Section: Introductionmentioning
confidence: 99%
“…Trabectedin has a complex mechanism of action, involving DNA binding [25,27], interference with transcription factor binding [24], and activation of the transcription-coupled nucleotide excision repair (NER) system to create lethal single-strand breaks in DNA [4,35]. The cytotoxicity of trabectedin has been demonstrated in several in vitro and preclinical studies involving a variety of cancer types [12,14,18,29,37].…”
Section: Introductionmentioning
confidence: 99%
“…It possesses potent antineoplastic activity against a variety of human tumor xenografts grown in athymic mice, including melanoma and ovarian and breast carcinoma. [1][2][3] In clinical phase 1 studies of ET-743, promising responses were observed in patients with sarcoma, as well as breast and ovarian carcinoma, 4,5 and the drug is currently under intense investigation in a variety of phase 2 trials in cancer patients. However, myelotoxicity is dose-limiting.…”
mentioning
confidence: 99%